Vaccine attitudes, practices, and literacy among New York State primary care providers and their office personnel - Manika Suryadevara; Dongliang Wang; Joseph Domachowske (Human Vaccines & Immunotherapeutics)
Consistency of the healthcare delivery team’s communication to families is influential in vaccine decision-making. We aim to describe personal vaccine practices, attitudes, and literacy among New York State primary care office providers and personnel. We disseminated an anonymous survey to providers and office personnel (including but not limited to front office staff, medical assistance, nurses, advanced practice providers, and physicians) of 12 primary care practices between May and July 2023. Responses were assessed using chi-square tests, t-tests, and one way ANOVA tests to compare categorical variables, the means between two groups, and means across multiple groups, respectively. 216 respondents completed the survey. 25/213 (12%) and 16/147 (11%) reported declining routinely recommended vaccine(s) for themselves or for their child(ren), respectively, most commonly the COVID-19 and/or influenza vaccines. Less than three-quarters of respondents strongly agreed with the following statements: vaccines are safe to administer to children (149/214, 70%), vaccines are safe to administer to adolescents (149/213, 70%), and vaccines are effective in preventing disease (146/213, 69%). In total, 149/213 (70%) and 89/211 (42%) of respondents report that parents express concerns to them about vaccines in the clinic and outside of the practice setting, respectively, yet just over half of the respondents (116/210, 55%) report strong agreement with being comfortable having vaccine conversations with parents. Vaccine hesitancy exists across all healthcare team roles. Practice-wide education regarding vaccine safety, efficacy and importance and strategies for communicating about vaccines with patients and families is needed to improve vaccine confidence among the healthcare teams and patients.